1999
DOI: 10.1080/000163599428535
|View full text |Cite
|
Sign up to set email alerts
|

Direction of shrinkage of light-curing resin composites

Abstract: It is occasionally stated in the dental literature that light-curing resin composites shrink towards the light source. As light travels at the speed of light, this dictum is not obvious. It was the purpose of the present study to investigate the direction of shrinkage of a light-curing resin composite in relation to the attachment and the thickness of the material. The resin composite was applied in cylindrical brass molds in such a manner that a flash, serving as attachment, was produced at one side of the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 13 publications
0
21
1
Order By: Relevance
“…Even in Group 1, which was applied without bonding agent, a small measurable surface depression was observed (Table 2). This observation contrasted that made by Asmussen & Peutzfeldt (1999), who reported shrinkage toward the light source for a specimen thickness of 3 mm. This difference may be explained by the difference in the number of cavity walls contacting the materials.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Even in Group 1, which was applied without bonding agent, a small measurable surface depression was observed (Table 2). This observation contrasted that made by Asmussen & Peutzfeldt (1999), who reported shrinkage toward the light source for a specimen thickness of 3 mm. This difference may be explained by the difference in the number of cavity walls contacting the materials.…”
Section: Discussioncontrasting
confidence: 55%
“…This difference may be explained by the difference in the number of cavity walls contacting the materials. The higher surface depression of the resin composite with maximal attachment to the cavity floor, as in Group 4, demonstrates that the direction of shrinkage not only depends on the specimen thickness and the presence or absence of a flash (Asmussen & Peutzfeldt, 1999), but also on the extent and quality of the attachment of the resin composite that directs the shrinkage of the resin composite toward a center near the interface. Therefore, bond quality must be regarded as a crucial factor in evaluating the direction of the shrinkage.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Light-cured composites are widely considered to show shrinkage oriented toward the irradiated surface of the restoration 3,15) . However, shrinkage in cavities is mainly influenced by adhesion, flow on the free surface, and local polymerization 5) .…”
Section: Introductionmentioning
confidence: 99%
“…In an in vitro study, Asmussen & Peutzfeldt 8) demonstrated that light-curing resin composites filled in a ring-shaped brass mold shrank towards the light source when the thickness of resin composite was less than that being cured in most clinical situations (< 2 ㎜). However, when an adequate bond quality was obtained at the bottom wall as well as the lateral walls, the light-curing resin composite did not shrink toward the light source during polymerization [7][8][9] . Because the bulk of the resin composite shrank toward a certain point between the center of the bulk and the cavity floor, the shrinkage of the polymerizing resin composite still exerted stresses on the adhesive layer at the cavity floor 9) .…”
Section: ⅰ Introductionmentioning
confidence: 99%